Evidence against tetrapod-wide digit identities and for a limited frame shift in bird wings - Thomas A. Stewart (Nature Portfolio, 2019)
The homology of digits across amniotes is debated. Here, the authors compare the developmental transcriptomes of digits across five divergent amniotes and show high evolutionary dynamism in expression profiles, with conservation of a distinct developmental identity only in the anterior-most digit.